Development of the Color Scale of Perceived Exertion: Preliminary Validation. Issue 3 (December 2014) - Serafim, Thais H. S.; Tognato, Andrea C.; Nakamura, Priscila M.; Queiroga, Marcos R.; Pereira, Gleber; Nakamura, Fábio Y.; Kokubun, Eduardo
This study developed a Color Scale of Perceived Exertion (RPE-color scale) and assessed its concurrent and construct validity in adult women. One hundred participants (18–77 years), who were habitual exercisers, associated colors with verbal anchors of the Borg RPE scale (RPE-Borg scale) for RPE-color scale development. For RPE-color scale validation, 12 Young ( M = 21.7 yr., SD = 1.5) and 10 Older ( M = 60.3 yr., SD = 3.5) adult women performed a maximal graded exercise test on a treadmill and reported perceived exertion in both RPE-color and RPE-Borg scales. In the Young group, the RPE-color scale was significantly associated with heart rate and oxygen consumption, having strong correlations with the RPE-Borg scale. In the Older group, the RPE-color scale was significantly associated with heart rate, having moderate to high correlations with the RPE-Borg scale. The RPE-color scale demonstrated concurrent and construct validity in the Young women, as well as construct validity in Older adults.